Optimization of PCR protocols for microsatellite markers in green lipped mussel, Perna viridis (Linnaeus, 1758) population at Tarangnan, Samar - Que, Riza Gemmae L. (2016.)
Perna viridis are cultured in many Asian countries as a source of protein, but are still in poor quality. Genetic characterization is one solution to identify good quality stock for aquaculture, but before characterization, optimization of PCR protocols for microsatellite markers must be studied. Microsatellite markers PCAN 2-17 and PCAN 1-25 which were designed for P. canaliculus by MacAvoy et. al. (2008) was used for P.viridis in this study. Ten samples were collected form Tarangnan, Samar. The PCR protocol for the reaction mix and cycling conditions were adapted and modified from Ong et. al. (2009). For PCAN 2-17, at optimum temperature of 55.6°C, different samples form Tarangnan were tested for predominant alleles and two consistent alleles were appearing with size range 729.9 ? 2,031.6bp in contrast to the 6 alleles noted form the Navotas samples. PCAN 1-25 had potentially estimated two alleles present with size range 255.1 to 421.4 bp at optimum annealing temperature of 56°C. Variation in the number of alleles due to DNA slippage was also observed. Thus, these results can be potentially used as molecular markers to characterize of P. viridis population in the Philippines.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Perna viridis; Perna viridis -- Characterization; Perna viridis -- Optimization; Perna viridis -- Population; Microsatellite; Tarangnan, Samar